Minimum Rate Regulation, Modal Split Sensitivities, and the Railroad Problem - Boyer, Kenneth D. (Journal of Political Economy, 1977)
Contrary to popular opinion, the diversion of traffic from railroads to motor carriers has not been the result of minimum rate regulation. The idea that there is a large amount of misallocated traffic is based on the widespread but faulty method of analyzing intermodal competition by means of a simple cost comparison. The paper uses modal split analysis to show that the welfare gain accompanying minimum rate regulation will be modest. The welfare effects of transport controls other than minimum rate regulations are likely to be far more serious.